The Effect of Mother Tongue toward English Pronunciation - Yusniati N Sabata; Depran Liise; ST. Marhana Rullu; Desriani Nggolaon; Nurhaida Lakuana (Applied Research on English Education (AREE), 2023)
The purpose of this research is to describe the differences between English and students’ transcriptions and factors affecting English pronunciation. The researcher used a qualitative research method in this research which consisted of five students of English Education Study Program of Muhammadiyah Luwuk who were from Banggainese as the subjects. In collecting data, the researcher used the interview as an instrument. The findings of this research showed there are some differences between English and students’ transcriptions, i.e. there are mispronunciations. One of the causes is the effect of the mother tongue. Additionally, the researcher also found that there are four factors affecting English pronunciation, they are: age, the first, language, the learners’ motivation and attitude, and the teachers’ instruction in the target language.